Determinants of Local Government Financial Performance - Maya Sari; Arum Aztisya (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2022)
This study aims to determine the determinants of local government financial performance in North Sumatra. This research is a type of associative research. The sampling technique was carried out using a saturated sampling technique. The sample obtained was 33 regencies/cities in the province of North Sumatra with a total of 165 observational data for 5 years of observation. The data collection technique used is documentation with data sources using secondary data taken through the official website of the Ministry of Finance DJPK. The data analysis technique used in this research is multiple linear regression analysis. The results of this study indicate that the factors that affect the financial performance of the regional government, namely local revenue, balancing funds, and capital expenditures, partially and simultaneously affect the financial performance of local governments